2020
DOI: 10.31160/jotci202028a20190034
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac catheterization with normal coronary arteries: prevalence rate and analysis of predictor variables

Abstract: Objective: To assess the percentage of patients with normal coronary angiography in a hospital and to determine the predictor variables of this finding. Methods: All elective coronary angiographies performed from April to October 2018 were analyzed, excluding patients with valve diseases and who had a previous catheterization. A total of 503 patients were recruited, divided into 2 groups: Group A for normal coronary arteries, and group B for coronary artery disease. Coronary vessels with diameter ≥2.0mm and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
6
1
2
Order By: Relevance
“…Also, our sample of 247 patients with angiographically normal coronary arteries was selected among 691 consecutive patients in whom other abnormalities had been excluded, and correspond to nearly 36% of such individuals who are referred for elective coronary angiography. This finding is inferior to 45% recently reported by another Brazilian hospital, 25 but is quite similar to the reported 39% of patients with coronary stenoses < 20% as the general yield by elective coronary angiography during the years 2004-2008 from an American College of Cardiology national registry. 26 …”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Also, our sample of 247 patients with angiographically normal coronary arteries was selected among 691 consecutive patients in whom other abnormalities had been excluded, and correspond to nearly 36% of such individuals who are referred for elective coronary angiography. This finding is inferior to 45% recently reported by another Brazilian hospital, 25 but is quite similar to the reported 39% of patients with coronary stenoses < 20% as the general yield by elective coronary angiography during the years 2004-2008 from an American College of Cardiology national registry. 26 …”
Section: Discussioncontrasting
confidence: 59%
“…Além disso, nossa amostra de 247 pacientes com artérias coronárias angiograficamente normais foi selecionada entre 691 pacientes consecutivos, nos quais outras anormalidades foram excluídas, e corresponde a quase 36% dos indivíduos encaminhados para angiografia coronariana eletiva no período. Esse resultado é inferior aos 45% relatado recentemente por outro hospital brasileiro, 25 mas é muito semelhante aos 39% de pacientes com estenoses coronárias < 20% submetidos à angiografia coronária eletiva entre os anos de 2004 e 2008, segundo o registro nacional do American College of Cardiology. 26 Com exceção da média de idade discretamente mais elevada no grupo DMC-OE, vale ressaltar que os dois grupos em nosso estudo apresentavam características antropométricas e clínicas essencialmente similares, incluindo uma maior prevalência do gênero feminino, pacientes ligeiramente obesos que, além da angina atípica, também se queixaram de dispneia e palpitações.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, previous studies, such as one by Shah et al, suggested that QCA tends to underestimate the diagnosis of obstructive CAD when compared to visual estimation. 11 This may have been one of the factors that contributed to the higher percentage of normal exams found by Sant'Anna et al 6 The prevalence of CAD found in previous studies, such as Ferreira et al and Levitti et al, were determined by visual estimation of the lesions, hindering direct comparison of findings. 7,8 In addition, previous studies have not shown a predictable correlation of severity of the obstruction estimated by QCA with the functional impact of the lesion measured by fractional flow reserve (FFR).…”
mentioning
confidence: 97%
“…5 Considering this basic scenario, the article published by Sant'Anna et al has great relevance, for it shows national data on the prevalence of elective coronary angiography with absence of obstructive lesions. 6 In the study, 503 consecutive patients with no anatomically known CAD underwent elective diagnostic coronary angiography in a private organization in Cabo Frio, in the state of Rio de Janeiro. Almost 90% of patients were from SUS units, stratified into two groups, according to presence or absence of significant obstructive CAD on coronary angiography.…”
mentioning
confidence: 99%